Amaryllidaceae: Potential Source of Alkaloids. Biological and Pharmacological Activities (2020)
Plants of Amaryllidaceae family have gained importance for being used as ornamentals, for having flowers and a showy appearance, in addition to their extensive pharmacological properties. The genera mainly studied are Amaryllis, Crinum, Galanthus, Narcisus, Bruganvigia and Lycoris. They produce alkaloids having as primary precursors L-phenylalanine and L-Tyrosine, which give rise to the main carbon skeleton called norbelladine, which through oxidation of the coupling of phenol, generates structures with ortho-para 'type positions, for - ortho 'and para - para', grouping the types of isoquinolic alkaloids, such as liquorine, homolicorin, crinine, haemantamine, tazetine, narcyclasin, montanin and galantamine. These alkaloids have antiviral, antimicrobial, cytotoxic, anticonvulsant, antitumor, hypotensive, and anti-inflammatory activity. The main alkaloid of this family is galantamine, being produced from the plants Leucojum sativum or Narcissus pseudonarcissus, and used therapeutically to inhibit the activity of acetylcholinesterase, counteracting the symptoms caused by the damage of the nervous system by Alzheimer's disease.